PERTANGGUNGJAWABAN PIDANA TERHADAP PENGEDAR SEDIAAN FARMASI TANPA IZIN EDAR DI APOTEK GAMMA MEDAN (Studi Kasus Putusan No.2753/Pid.B/2013/PN.MDN) - Taufiq Ramadhan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
The distribution of pharmaceutical preparations has now reached the stage of being easy to obtain, social media such as Instagram and line can be said to be a factor in the distribution of pharmaceutical preparations without permission until they reach freelance sales and then distributed to pharmacies. Pharmacies accept these pharmaceutical preparations by the reason that they are cheap and easy to obtain and without a letter of order and purchase invoice. Pharmacies that procure pharmaceutical preparations not through parties mentioned by the law such as pharmaceutical wholesalers certainly do not have official documents such as an order letter that has been signed by APA and an order invoice, this act violates the provisions in Article 106 of Law No.36 Year 2009 concerning health and threatened with criminal in accordance with Article 197 of Law No. 36 of 2009 concerning health such as dealers who are the owners of the Gamma Medan Pharmacy as stated in the decision  No. 2753/Pid.B/2013/PN.MDN. How is the regulation of criminal law against the distribution of pharmaceutical preparations without a permit, how is the criminal responsibility for the distributors of pharmaceutical preparations without a distribution permit at Gamma Medan Pharmacy (Case Study Decision No.2753/Pid.B/2013/PN.Mdn), what is the role of Civil Servant Investigators BBPOM is in the process of resolving cases of distribution of pharmaceutical preparations without a distribution permit. Criminal law regulations on the distribution of pharmaceutical preparations without a distribution permit can be found in the Criminal Code, Law No. 5 of 1997 concerning Psychotropics, Law No. 8 of 1999 concerning Consumer Protection, Law No. 36 of 2009 concerning Health, Law No. 35 of 2009 concerning Narcotics and PP RI No. 72 of 1998 concerning the Security of Pharmaceutical Preparations and Medical Devices. Distributors of pharmaceutical preparations without a distribution permit can be charged with criminal responsibility against them because based on their mistakes have violated Article 106 paragraph (1) Law no. 36 of 2009 concerning Health and has completed the elements in Article 197 in conjunction with Article 106 paragraph (1) of the Law of the Republic of Indonesia No. 36 of 2009 concerning Health for the act of deliberately distributing pharmaceutical preparations without a distribution permit and sentenced to imprisonment of 1 (one) year. ) months and 15 (fifteen) days and a fine of Rp.5.000.000,- (five million rupiahs) provided that if the fine is not paid, it is replaced with imprisonment for 1 (one) month. The role of Civil Servant Officials in the Settlement of the cases of the distribution of pharmaceutical preparations without a distribution permit is as Investigators. The government should provide facilities to investigators in resolving cases of distribution of pharmaceutical preparations without a permit, such as assistance by the police, supporting facilities and infrastructure as well as additional special criminal procedural law education for investigators because some investigators are not legally educated but pharmacists.Keywords: Criminal Liability, Pharmaceutical Preparations, Without Distribution Permit.